Yan! Kaka-cellphone mo yan! an analysis of social media and its effects on HIV/AIDS awareness among youth in the Philippines - Fabi, Kayla S. (School of Economics, University of the Philippines Diliman, 2018)
The rising HIV or AIDS cases in the Philippines is a growing public health concern. From May 2017, the number of HIV_positive individuals recorded by the Department of Health has increased by almost 50 percent from the previous year. This growth may be attributed to the lack of awareness and comprehensive knowledge on HIV or AIDS, especially among the youth. This thesis explores the relationship between social media use and HIV or AIDS awareness among Filipino youth. Using cross sectional data from the 2015 National Youth Assessment Survey by the National Youth Commission, the researchers conducted a logistic regression analysis using three models to determine the effect of social media and other demographic characteristics on awareness of HIV or AIDS. The first model only included variables on technology access, the second model included variables on technology access and socio_demographic characteristics, and the third model included variables on both and accounted for distribution of respondents across the regions. Across all three models, the number of internet access points had a strong positive relationship with HIV or AIDS awareness _ that is, an increase in the number of internet access points also increases the likelihood of an individual having HIV or AIDS knowledge.